Green Synthesis, Characterization, and Antimicrobial Activity of Carbon Nanoparticles Derived From Mustard Oil - Tamang, Samyamta; Subedi, Reshma; Thapa, Nabin Kumar; Mitruka, Jay Narayan; Chapagain, Subas Kumar; Bhattarai, Ajaya (Amrit Research Journal, 2025)
In this study, carbon nanoparticles (CNPs) were made from mustard oil using the principles of green chemistry. Green chemistry employs a low-cost, straightforward combustion method that eliminates the need for potentially dangerous components. The characterization techniques used in this study were Fourier Transform Infrared (FTIR) Spectroscopy and X-ray diffraction (XRD). FTIR spectroscopy examination verified the presence of carbon nanoparticles by identifying the presence of C=O, C-H, O-H, C-O, and C-C bonds in the sample. The carbon nanoparticles produced were shown to be amorphous by XRD analysis. Nevertheless, the antibacterial activity of generated carbon nanoparticles was effective when tested on Bacillus subtilis, E. coli, and fungus.